2008
DOI: 10.1063/1.2905562
|View full text |Cite
|
Sign up to set email alerts
|

How Efficient is Rotational Mixing in Massive Stars ?

Abstract: Abstract. The VLT-Flames Survey for Massive Stars [1,2] provides precise measurements of rotational velocities and nitrogen surface abundances of massive stars in the Magellanic Clouds. Specifically, for the first time, such abundances have been estimated for stars with significant rotational velocities. This extraordinary data set gives us the unique possibility to calibrate rotationally and magnetically induced mixing processes. Therefore, we have computed a grid of stellar evolution models varying in mass, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…As it must, the effect vanishes for Sc → 0. Schatzman suggested such a relation D T = Re * ν with Re * =O(100) in order to explain diffusion processes in radiative zones of stars [166,167,168,169]. Obviously, the factor Re * , which in a wider sense can be considered as a microscopic Reynolds number (of a pattern cell) can be computed as due to magnetic instability with the presented models.…”
Section: Mixing Of a Passive Scalarmentioning
confidence: 98%
“…As it must, the effect vanishes for Sc → 0. Schatzman suggested such a relation D T = Re * ν with Re * =O(100) in order to explain diffusion processes in radiative zones of stars [166,167,168,169]. Obviously, the factor Re * , which in a wider sense can be considered as a microscopic Reynolds number (of a pattern cell) can be computed as due to magnetic instability with the presented models.…”
Section: Mixing Of a Passive Scalarmentioning
confidence: 98%
“…In the stellar interior, carbon is converted into nitrogen, which can reach the surface due to mixing and/or mass loss. Brott et al (2008) found that the surface nitrogen abundance can be enhanced by a factor of 11 with a realistic initial SMC mixture. A Solar-scaled mixture with the same iron abundance would lead to enhancement of only a factor of 4, for the same initial parameters.…”
Section: The Initial Chemical Compositionmentioning
confidence: 99%
“…The turbulent viscosity generated by the AMRI can be very effective at transporting angular momentum (Rüdiger et al 2015), with the magnetic contribution due to Maxwell stresses strongly dominating over the kinetic component. As a consequence, mixing is much less enhanced by the AMRI than angular momentum transport, and the Schmidt number (the ratio of turbulent viscosity and turbulent element diffusion coefficient) is large enough not to speed up stellar evolution significantly Schatzman (1977), Lebreton & Maeder (1987), Brott et al (2008). A distinctive property of the AMRI-induced viscosity is its dependence on the angular velocity shear present in the region where the instability develops.…”
Section: Introductionmentioning
confidence: 99%